Morphometric differentiation of Glossophaga soricina soricina (Chiroptera: Phyllostomidae) in three Brazilian biomes - Louzada,Nathália S. V. (2013)
Glossophaga soricina soricina (Pallas, 1766) plays an important role in the ecosystems where it is found, taking part in the pollination of hundreds of plant species. Here, we statistically compared 12 external characters of 169 specimens collected in three Brazilian biomes: 82 in the Pantanal (Mato Grosso), 45 in the Atlantic Forest (Ilhéus, Bahia) and 42 in the Caatinga (Chapada Diamantina, Bahia). Each character was analyzed by descriptive and inferential statistics. The t-test didn't detect any differences between males and females of each population. The ANOVA with a posteriori Tukey test showed significant results for all traits (Forearm length, Calcar length, Body length, Tail length, Hindfoot length, Ear length, Tragus length, Thumb length, Noseleaf length, Noseleaf width and Horseshoe width) except for Tibia length. The discriminant analysis showed distinct clusters representing the populations of each biome. The tests demonstrated that the three populations are significantly different from one another and that the specimens of the population from the Caatinga, on average, are larger than those from the Pantanal, which are larger than those from the Atlantic Forest, confirming the possible existence of intra-specific geographic variation.